asas - Stanley Darwinus Jayadi; Neva Sefanya; Valencia Pranoto; Meike Kurniawati (LPPM Universitas Buddhi Dharma, 2025)
Lifestyle changes and easy access to various financial services have had a significant impact on spending behavior, especially in early adulthood. At this time, individuals begin to manage finances independently but are faced with challenges in managing personal finances amidst increasing needs and desires influenced by social trends and consumptive lifestyles. This study aims to determine the effect of financial management on spending behavior in early adult individuals. The study used a quantitative approach with a survey method involving 73 respondents aged 18 to 25 years selected by convenience sampling technique. The data collection instrument was a questionnaire with a five-point Likert scale. The results of the analysis showed that most participants had a low level of financial management, while the level of spending behavior was quite high. However, the simple linear regression test results show that financial management does not have a significant influence on spending behavior (significance value > 0.05). The coefficient of determination of 0.033 indicates that only 3.3% of spending behavior variables can be explained by financial management, while the rest is influenced by other factors not examined in this study. This finding suggests that spending behavior in early adulthood is not directly influenced by how well they manage their finances. Therefore, it is important for future research to consider psychological, social, cultural, and financial literacy factors in examining spending behavior in the younger generation more comprehensively.